Pemberdayaan UMKM Keripik Singkong Berbasis Wakaf Produktif Melalui Pendampingan Dan Analisis SWOT Di Desa Karangharjo Kabupaten Jember - Ulum, Bachrul; Fatmawati, Fatmawati; Kalamiah, Moh. Jeweherul (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Productive waqf is a waqf concept that not only functions as a donation for religious or social purposes, but is also managed professionally to generate profits that can be used to improve the community's economy. This study focuses on the management of productive waqf in the wider community in Jember Regency which can make a real contribution to the local economy. This study aims to analyze the strategy for developing productive waqf in order to improve the community's economy through a qualitative descriptive approach using SWOT analysis and direct observation. The results of the study identified several main strategies to improve the community's economy, including waqf asset management methods, accessible economic sectors and the long-term economic impacts resulting from the implementation of productive waqf. Management of waqf assets carried out professionally can have a significant impact on the wider community, while potential economic sectors to be developed can increase waqf asset funds. The implementation of productive waqf carried out continuously will have a good economic impact for a long time. The novelty of this activity lies in the integration of the concept of productive waqf as a source of capital strengthening and governance for cassava chip MSMEs, combined with participatory mentoring and SWOT analysis based on local village potential. The resulting tangible impact is not only increased business capacity and product competitiveness, but also the creation of a sustainable economic empowerment model that can be replicated by other village MSMEs in Jember Regency. These findings are expected to help improve the economy of the wider community in Jember Regency through the implementation of productive waqf effectively and professionally